Additional radiation sources in a treatment and control room of medical linear accelerators. (August 2021) - Konefał, Adam; Bieniasiewicz, Marcin; Wendykier, Jacek; Adamczyk, Sebastian; Wrońska, Aleksandra
Abstract: Typical medical linear accelerators generating high-energy photon beams used in radiotherapy are a source of neutrons and induced radioactivity undesirable mainly in radiological protection of medical staff but also for treatment of patients. The main source of the secondary radiation are massive components of an accelerator head. The purpose of this work was to study additional sources of gamma rays and neutrons in the treatment and control rooms for the Elekta accelerator. Identification of radioisotopes induced in several examined objects used and stored in the treatment room, and measurements of the spectrum of gamma rays originated in the treatment room door or travelling through it were carried out using a gamma–ray spectroscopy technique with an HPGe detector. Additionally, identification of neutron field was performed in the control room. In total, five nuclear reactions and five radioisotopes Mn-56, Sb-122, Fe-59, Li-7 and Al-28 were identified basing on gamma rays from the radioactive decays in the 20 cm × 20 cm electron applicator enabling collimation of the therapeutic electron beam, a Wood's alloy tray used as an additional shield against radiation, a special drawer for placing additional radiation shields, and a brick used to shield electronic modules of supporting equipment. Similarly, five nuclear reactions were also observed registering prompt gamma rays in the control room. The dominating nuclear reaction was the neutron capture. Moreover, the reactions induced by neutrons in the germanium crystal of the used HPGe detector confirmed the presence of neutrons in the control room. Highlights: The sources of the secondary radiation were investigated for the medical accelerators Elekta. The research was performed using gamma-ray spectroscopy. The study was related to radiation induced in a door to a treatment room and some accessories of the Elekta. In total 9 radioisotopes originating from neutron reactions were identified. A weak neutron field in the control room was identified by the neutron response in the HPGe detector.